Experiment in vivo: How COVID-19 Lifestyle Modifications Affect Migraine - Grozeva, Vesselina; Mínguez-Olaondo, Ane; Vila-Pueyo, Marta (Frontiers in Neurology, 2021)
IINTRODUCTION: COVID-19 pandemic represents a unified lifestyle modification model, which was developed by the globally applied measures. The lockdowns designed the perfect study settings for observing the interaction between migraine and the adopted changes in lifestyle. An experiment in vivo took place unexpectedly to determine how the lockdown lifestyle modifications can influence migraine. LIFESTYLE MODIFICATIONS DURING PANDEMIC: People stay home and outdoors activities and public contacts are restricted. Sleep is disturbed. Media exposure and prolonged screen use are increased. Working conditions change. In-person consultations and therapies are cancelled. The beneficial effects of short-term stress, together with the harmful effects of chronic stress were observed during the pandemic. SHORT-TERM EFFECTS: Substantial lifestyle changes happened and knowing how vulnerable migraine patients are, one could hypothesize that this would have resulted in severe worsening of headache. Surprisingly, even though the impacts of changing social conditions were significant, some patients (including children) experienced a reduction in their migraine during the first lockdown. LONG-TERM EFFECTS: Unfortunately, headache frequency returned to the basal state during the second pandemic wave. The risk factors that could have led to this worsening are the long-term disruption of sleep and dietary habits, stress, anxiety, depression, non-compliance to treatment, and working during the pandemic. DISCUSSION: Sudden short-term lifestyle changes taking migraine patients out of their usual routine may be beneficial for headache management. It is not necessary to have a natural disaster in place for a drastic lifestyle modification with 6-8 weeks duration, if we know that this will improve migraine.